International advances in self-direction: themes from a disability leadership exchange. Issue 3 (2nd March 2021) - Bradley, Valerie; Kwak, Miso; Rich, Highsmith; Croft, Bevin
Abstract : Purpose: Self-direction–also known as participant direction, personalization and self-directed care–is a service delivery model that enables people to manage their personal budget and purchase services and supports tailored to their needs based on a person-centered plan. This paper, the outcome of an international learning exchange on self-direction, describes approaches across four countries' successful strategies, unresolved questions and recommendations to enhance self-direction globally. Design/methodology/approach: The findings are a product of discussions at the 2019 International Initiative for Mental Health Leadership and International Initiative for Disability Leadership Exchange on Advances in Self-Direction. Participants included people who are self-directing, providers and caregivers who support people who are self-directing, advocates, fiscal agents and public managers who administer self-direction from the United States, England, Australia and New Zealand. Findings: In all four countries, people who self-direct exercise high levels of choice and control and are able to individualize their services and supports to promote a good life in the community. The exchange also revealed challenges and possible solutions to improve and expand self-direction. Practical implications: The results of the meeting provide guidance for public managers, providers and advocates for initiating and expanding self-direction. Originality/value: This international meeting was a unique opportunity to compare self-direction across four different countries and across multiple perspectives, including people with disabilities, caregivers, providers and administrators.